(3LGeY GdeSGfjO hGdCdbGHs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf LeGYI ef GUMGHfG GdabgGA CMHhG GdEWdGY Ydi MOjK QShd Gddg Udi Gddg Ydjg hSde hQChG GdGMGOjK eJcQQI ai GdcJH hCdaGXgG JfbU hJRjO s
(3BNQgG (B:s
(3jfJgi Edi GdMOjK GdSGHY hGdKdGKjf HYO GdeGFI ef eSfO CHj SYjO SYO Hf eGdc GdNOQi s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B573s
Keywords: (3GdMOjK h GdeUWdMs